Takhrij and Syarah Hadith of Agrotechnology: Ingredients and Benefits of Black Cumin for Health - Nasya Aulia Yusup Safitri; Wahyudin Darmalaksana; Safarinda Nurdianawati (Gunung Djati Conference Series, 2021)
The purpose of this study is to discuss the hadith of the Prophet Muhammad about black cumin. The method used in this research is a qualitative type through literature study and field studies with the approach of takhrij and sharah hadith agrotechnoogy. The results and discussion of this research are black cumin plants popular during the time of the Prophet Muhammad and is known to have many properties. The conclusion of this research is takhrij and syarah hadith of the Prophet about black cumin plants as herbal medicine for all diseases in the era of the Prophet, not the treatment of all diseases in today's modern era.